Selection of Sugars for Cryoprotective Media on MCF-7 Breast Cancer Cell Cultures - Kopiak, Bohdan; Perepelitsina, Olena; Sydorenko, Mykhailo (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):299